Comprehensive Overview of Modern Controllers for Synchronous Reluctance Motor - S. AngayarKanni; K. Ramash Kumar; A. Senthilnathan (Journal of Electrical and Computer Engineering)
Synchronous reluctance motor drives (SynRMs) are the best promising machines utilized in modern industries and electric vehicles, according to the current study. Research on new SynRMs drive systems has increased as a result. This review article disseminates the most recent developments in these technologies’ design, modeling, and controlling. First, a simple comparison between the main motor technologies and SynRMs is made. To aid researchers in selecting the appropriate motor controller for their motor drive systems, the most common motor control approaches are examined and classed.